2014
DOI: 10.1016/j.jcrs.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

High-irradiance accelerated collagen crosslinking for the treatment of keratoconus: Six-month results

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
67
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 20 publications
3
67
0
2
Order By: Relevance
“…Elbaz et al retrospectively studied the efficacy of accelerated CXL in 16 keratoconus-affected eyes and reported the effectiveness of this procedure for the stabilization of topographic parameters, including Ksteep, Kflat, average K, corneal astigmatism, and maximal curvature reading at the corneal apex, after 12 months of follow-up (14) . Mita et al also evaluated the effectiveness of accelerated CXL in 39 eyes and reported significantly improved UCVA and Kmax values at 6 months after treatment (15) . The maximum keratometry value (Kmax or AKf ) has been considered a key topographic indicator of CXL success, and has been reported as stable or decreased after CXL in many studies (3,(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbaz et al retrospectively studied the efficacy of accelerated CXL in 16 keratoconus-affected eyes and reported the effectiveness of this procedure for the stabilization of topographic parameters, including Ksteep, Kflat, average K, corneal astigmatism, and maximal curvature reading at the corneal apex, after 12 months of follow-up (14) . Mita et al also evaluated the effectiveness of accelerated CXL in 39 eyes and reported significantly improved UCVA and Kmax values at 6 months after treatment (15) . The maximum keratometry value (Kmax or AKf ) has been considered a key topographic indicator of CXL success, and has been reported as stable or decreased after CXL in many studies (3,(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…Mita et al also evaluated the effectiveness of accelerated CXL in 39 eyes and reported significantly improved UCVA and Kmax values at 6 months after treatment (15) . The maximum keratometry value (Kmax or AKf ) has been considered a key topographic indicator of CXL success, and has been reported as stable or decreased after CXL in many studies (3,(15)(16)(17) . Similarly, we also observed significantly decreased AKf values after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…23 Similarly, variable results (0.06-0.8 D) were obtained in adult groups following accelerated corneal CXL. 15,25 Another finding of our study was that the number of patients whose progression did not halt was higher in the pediatric group (5/41) compared to the adult group (2/47). This is probably due to the fact that keratoconus is more aggressive at pediatric ages.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies did not identify any endothelial toxicity in accelerated corneal CXL. 8,15 Another limitation of the study is that we measured the aberration using Pentacam. According to the literature, there are conflicting data on the repeatability of Pentacam in the measurement of aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation